ACCLIMATIZATION OF CATTLEYA (ORCHIDACEAE) IN DIFFERENT CONTAINERS - Sorace, Mauren; Faria, Ricardo Tadeu de; Fonseca, Inês Cristina de Batista; Padovanni, Nathália; Ecker, Arney Eduardo do Amaral (Varia Scientia Agrárias, 2012)
Orchids are among the most cultivated ornamental plants in the world. Root formation and vegetal development of orchid Cattleya loddigesiii and hybrid Cattleya intermedia x Hadrolaelia purpurata (Orchidaceae) were evaluated using different recipients during the acclimatization phase. Seedlings, mean height 3±0.5 cm, were obtained from in vitro grown seeds in Murashige & Skoog (1962) culture medium and with half the macronutrient concentration. They were cultivated in different types of containers with sphagnum as their substratum. Recipients consisted of a plastic tray with 120 cells, polystyrene tray; earthenware tray and a transparent plastic tray with lid. Seedlings were maintained in a 60% luminosity greenhouse. A randomized design with four treatments and four replications was prepared with twenty plants per container as a statistical model. Seven months after the start of the experiment, the following factors were evaluated: frequency, length on biggest root; number of roots; height; length of the largest leaf; number of leaves; number of sprouts and total fresh mass. The plastic trays with 120 cells produced the highest vegetal growth and roots of Cattleya loddigesii seedlings and Cattleya intermedia x Hadrolaelia purpurata hybrid during the acclimatization stage.